Peranan Overthinking terhadap Kecemasan Sosial Mahasiswa yang Mengalami Impostor Syndrome - Muslimah, Najla Nada; Sahrani, Riana (YASIN, 2025)
Social anxiety is one of the mental health problems frequently experienced by university students and affects both academic processes and social life on campus, particularly when it intersects with a tendency toward overthinking and experiences of impostor syndrome. This study aimed to analyze the role of overthinking in social anxiety among students experiencing impostor syndrome. The research involved 385 students aged 18–25 years (135 male and 250 female), who were first screened using the Clance Impostor Phenomenon Scale (CIPS) to ensure that participants indeed experienced impostor syndrome. Overthinking was measured using the Ruminative Response Scale (RRS), while social anxiety was measured using the Social Anxiety Scale for Adolescents (SAS-A). A quantitative approach with simple linear regression analysis was employed. The results showed a significant role of overthinking in social anxiety, with R = 0.531, R² = 0.282, F = 150.484, and p = 0.000 < 0.05, indicating that the higher the level of overthinking, the higher the social anxiety among students experiencing impostor syndrome, with a contribution of 28.2%. These findings underscore the importance of paying attention to overthinking as a psychological factor contributing to increased social anxiety in students with impostor syndrome and indicate the need for psychological interventions focused on managing ruminative thinking patterns to support students’ mental health and academic functioning.